Jenis-Jenis Tumbuhan Lokal yang Dimanfaatkan Sebagai Bahan Baku Pembuatan Peralatan dalam Pengolahan Sagu (Metroxylonsp) - Sanito, Raynard Christianson (Universitas Muhammadiyah Surakarta, 2017)
Sago (Metroxylon sp) is the native plant species from South East Asia which is consumed by Sentani TribeatJayapura District, Papua, as a staple food. There are some species of Sago plants that consumed by SentaniTribe, such as Spineless Sago (Metroxylon sago) and Thorny Sago (Metroxylon rumpii). Mostly, in theprinciple the processing of Sago into Papeda still usingsometraditional equipments which made fromdifferent type of woods from various local plants species in Papua. This research’s aim to analyse the localplants that are used bypeople as their raw materials for making traditional equipments with the aim ofsupporting the process from the sago into Papeda for consumption.The methods were used in this researchwith observation and interview to primary informant and complementary informant. Based on theobservations and interviews with primary informant and complementary informant at the field, there werethree species of local plants that the woods are usedby Sentani Ethnic as the material for traditionalequipments in the process of sago into Papeda. The endemic plantwas used as a material such as Sowang(Xanthostemon novoguineensis) from Myrtaceae family. Other two species of native plantsconsist ofFabaceae family that known as Merbau (Intsia bijuga) and Myristicaceae family such as Nutmeg(Myristicafatua). The woods of Merbau, Sowang and Nutmegwere used as some equipments for raw materials in sagoprocessing such as axe and the food utensils like forkand particularlythe instrument for inverting orrotatingPapeda.